Meningkatkan Hasil Belajar Dengan Metode PBL Fase C Kelas 6 di SDN 23 Tikalong Kabupaten Landak - Rohana Rohana; Hartutik Hartutik (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
The main issue in Catholic Religious Education (PAK) learning in Grade VI of SD Negeri 23 Tikalong, Landak Regency, West Kalimantan, is the lack of student participation and engagement. The teacher tends to apply a lecture-based approach that minimally involves students, resulting in low learning outcomes. This study aims to examine the improvement in students’ independence and achievement in PAK learning through the implementation of the Problem Based Learning (PBL) model. The study focuses on strengthening the independence dimension of the Pancasila Student Profile, with the goal of enhancing students’ affective development throughout the learning process.This research adopts a Classroom Action Research (CAR) approach, carried out in two cycles, each consisting of planning, action, observation/evaluation, and reflection stages. The research subjects were two sixth-grade students. The observed learning outcomes covered cognitive, affective, and psychomotor domains. Prior to the intervention, the percentage of students achieving the minimum mastery criteria (KKM = 75) was only 30%. The findings show a significant improvement in cognitive performance: the average score increased from 75 in Cycle 1 (with 50% in the “competent” category) to 80 in Cycle 2 (with 50% in the “proficient” and 50% in the “competent” categories). Student independence also increased from 77% in Cycle 1 to 100% in Cycle 2. Reflections during the research suggest the need for affective support to optimize students’ overall learning outcomes. In conclusion, the implementation of the PBL method proved effective in enhancing Catholic Religious Education learning outcomes and student independence in Grade VI.